Monkeys (Macaca fascicularis) with rhinal cortex ablations succeed in object discrimination learning despite 24-hr intertrial intervals and fail at matching to sample despite double sample presentations. - Gaffan, D; Murray, E (1992)
Six cynomolgus monkeys (Macaca fascicularis) learned preoperatively a set of 10 concurrent object discriminations with 24-hr intertrial intervals. Three then had the rhinal cortex removed bilaterally, whereas the other 3 remained as unoperated controls. The animals with ablations were impaired in reacquiring the preoperatively acquired set but subsequently learned without any impairment a new set of 10 discriminations that was presented in the same way. The monkeys with rhinal cortex ablations then failed to learn delayed matching to sample, with double sample presentations, in 510 trials, whereas the control animals learned this task in 270 trials on average. The results add to existing evidence that rhinal cortex ablation produces a severe impairment in visual short-term recognition memory and show for the first time that this impairment is accompanied by normal long-term discrimination learning ability.